Pengaruh Pupuk Urea terhadap Produksi dan Pertumbuhan Rumput Odot (Pennisetum purpureum cv Mott) - Daryatmo, Joko; Mubarokah, Wida Wahidah; Budiyanto, B (Fakultas Peternakan Universitas Papua, 2019)
This study aims to determine the effect of 4 doses of urea fertilizer on production and growth of Odot grass (Pennisetum Purpureum cv. Mott). The experimental design used was a completely randomized design (CRD) pattern in line with 4 treatments and each treatment consisted of 5 replications. The treatment used is Control (P0), urea at a dose of 100 kg/ha (P1), urea at a dose of 150 kg/ha (P2), urea at a dose of 200 kg/ha (P3). The parameters observed were number of tillers, stem length, leaf length, grass height and grass production. The results of statistical analysis showed that the treatment of urea fertilizer had no significant effect on plant height. The treatment of urea fertilizer had a significant effect (P<0.05) on number of tillers, stem length, leaf length and grass production. It can be concluded that the administration of urea fertilizer can increase the number of tillers, stem length, leaf length and odot grass production compared to odot grass that is not given urea fertilizer. Keywords: Urea, Fertilizer, Growth, Production, Pennisetum purpureum cv Mott